The Learning Gap in Islamic Religious Education in the Digital Era - Hamirudin (IAIN Ambon, 2023)
This research aims to explore the picture that occurs in Islamic Religious Education learning in the era of digitalization. This research is library research, using literature analysis from various sources on the internet. The results of the analysis in this research show that there are gaps in the implementation of PAI learning caused by various factors, including limited access to technology, lack of digitalization abilities or skills among educators and students, as well as uneven digital resources. The results of this research also suggest that a holistic approach needs to be taken in order to overcome this gap, including increasing access to technology, conducting digital skills training for educators, as well as developing digital-based learning content which is of course expected to be in accordance with the PAI curriculum.